Infant and Adult Brains Are Coupled to the Dynamics of Natural Communication. (January 2020) - Piazza, Elise A.; Hasenfratz, Liat; Hasson, Uri; Lew-Williams, Casey
Infancy is the foundational period for learning from adults, and the dynamics of the social environment have long been considered central to children's development. Here, we reveal a novel, naturalistic approach for studying live interactions between infants and adults. Using functional near-infrared spectroscopy (fNIRS), we simultaneously and continuously measured the brains of infants ( N = 18; 9–15 months of age) and an adult while they communicated and played with each other. We found that time-locked neural coupling within dyads was significantly greater when dyad members interacted with each other than with control individuals. In addition, we characterized the dynamic relationship between neural activation and the moment-to-moment fluctuations of mutual gaze, joint attention to objects, infant emotion, and adult speech prosody. This investigation advances what is currently known about how the brains and behaviors of infants both shape and reflect those of adults during real-life communication.